Use of intravitreal bevacizumab among patients undergoing retinal surgical interventions in a military hospital: a descriptive cross-sectional study (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Bevacizumab, a monoclonal antibody that hinders the activity of vascular endothelial growth factor, is extensively utilized within the field of ophthalmology. The utilization of Bevacizumab, particularly in retinal surgeries, lacks comprehensive investigation. The objective of this study is to determine the prevalence of intravitreal Bevacizumab usage in retinal surgical procedures conducted at a tertiary care center.Method: A retrospective descriptive cross-sectional study was conducted among patients who underwent retinal surgical interventions at a tertiary care center in Nepal. Data of patients who underwent retinal surgical interventions from 14 April 2022 to 16 November 2023 were collected from hospital records. The study employed a convenience sampling method. Data analysis was conducted using Statistical Package for Social Sciences (SPSS) Version 20. The point estimate was computed at a 95% Confidence Interval.Result: Among 1674 different ocular surgeries, intravitreal Bevacizumab injections were used in 453(27.06%) at 95% CI (24.94-29.19) patients. Central Retinal Vein Occlusion (CRVO) was identified as the predominant indication, accounting for 249(54.97%) patients. A majority of injections were administered to a single eye, accounting for 381(84.11%) patients. Additionally, 194(42.83%) patients received Bevacizumab as a one-time treatment.Conclusion: The prevalence of intravitreal Bevacizumab use among patients undergoing retinal surgical procedures was observed to be comparatively lower than that reported in previous studies conducted in similar settings. Central Retinal Vein Occlusion (CRVO), Choroidal Neovascular Membrane, and Central Serous Retinopathy were the most prevalent retinal diseases requiring intravitreal Bevacizumab intervention.